An Overview of Tectonic and Sedimentation Inter-relationship - F. Hasan Sidi; Herman Darman (Berita Sedimentologi, 1998)
For more than a century geoscientists had related tectonic to sedimentation by associating geosynclines with thick accumulations of sedimentation. Until the middle of 20th century, sedimentary basins were still rationalized and classified in terms of geosynclinal theory, including the publication of "Geology of Indonesia" in 1949 by R.W. van Bemmelen. The advent of plate tectonic theory led to a revival interest of tectonic and sedimentation since the development of this theory had provided fresh perspectives to build and constraint models of deep lithospheric behavior. Most of the sedimentary basins can now be explained in terms of plate-margin processes and consequently make the structure and stratigraphy have become more understandable. The plate tectonic theory demonstrated that one of the most important controls on sedimentation and deformation is the position of a sedimentary basin relative to either a plate or a continent-ocean boundary.